Profil Pelajar Pancasila Sebagai Implementasi Nilai Moral Peserta Didik Sekolah Dasar - Wardani, Tensya; Indah Triliyani; Desi Masayu Putri; Firma Andrian; Satria Nugraha Adiwijaya (PGMI IAIN Lhokseumawe, 2024)
Inculcation of moral values at the earliest opportunity as an effort to increase the student moral. That effort can be a learning benchmark for the teacher by implementation of Pancasila student profiles. Therefore the objective of this research is to analyze the Pancasila student profiles as an implementation for moral values of elementary students. This research used descriptive qualitative method at SD N 03 Metro Barat 2023. The data collecting technique is a questionnaire with questionnaire assessment instrument, the indicator that based on Kemendikbud 2021. The guarantor of data validity used triangulation. Then, the data was used by Miles and Huberman model that are data reduction, data serving, and conclusion creating. The result of this research shows that the student moral value is decrease time by time. The researcher found that there was limited control from the school, so the teacher could not know whether the student continues do the implementation of Pancasila student profiles or not.